2009
DOI: 10.1371/journal.pone.0006458
|View full text |Cite
|
Sign up to set email alerts
|

Punicic Acid a Conjugated Linolenic Acid Inhibits TNFα-Induced Neutrophil Hyperactivation and Protects from Experimental Colon Inflammation in Rats

Abstract: BackgroundNeutrophils play a major role in inflammation by releasing large amounts of ROS produced by NADPH-oxidase and myeloperoxidase (MPO). The proinflammatory cytokine TNFα primes ROS production through phosphorylation of the NADPH-oxidase subunit p47phox on Ser345. Conventional anti-inflammatory therapies remain partially successful and may have side effects. Therefore, regulation of neutrophil activation by natural dietary components represents an alternative therapeutic strategy in inflammatory diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 63 publications
1
90
0
4
Order By: Relevance
“…In 2014, Matthaiou et al (3) also determined that glutathione (GSH) levels were increased following two weeks PJ supplementation, indicating that PJ induced beneficial changes in erythrocyte antioxidant concentration. In 2009, Boussetta et al (24) reported that punicic acid, a conjugated unsaturated fatty acid which is derived from the oil of pomegranate seeds, has anti-inflammatory action due to its potential to reduce the activity of neutrophils. Specific tannins in pomegranate also exhibited anti-inflammatory action in mice (25).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Matthaiou et al (3) also determined that glutathione (GSH) levels were increased following two weeks PJ supplementation, indicating that PJ induced beneficial changes in erythrocyte antioxidant concentration. In 2009, Boussetta et al (24) reported that punicic acid, a conjugated unsaturated fatty acid which is derived from the oil of pomegranate seeds, has anti-inflammatory action due to its potential to reduce the activity of neutrophils. Specific tannins in pomegranate also exhibited anti-inflammatory action in mice (25).…”
Section: Introductionmentioning
confidence: 99%
“…Five CLnA isomers at least have been found in nature: α-eleostearic acid (9c,11t,13t-C18:3n-3), catalpic acid (9c,11t,13c-C18:3n-3), calendic acid (9c,10t,12c-C18:3n-3), jacaric acid (8c,10t,12c-C18:3n-3) and punicic acid (9c,11t,13c-C18:3n-3) (Koba et al, 2007). CLnA isomers have been attributed to exhibit several health benefits that are largely based on animal and in vitro studies (Boussetta et al, 2009;Hontecillas et al, 2009;Hennessy et al, 2011;Saha and Ghos, 2012;Yuan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in an experimental animal study, Binyamin et al proposed that nano-drop formulation of PSO might be considered for the treatment of demyelinating diseases due to its antioxidant effect [29] . It has been proposed that consumption of large amounts of CFA by the Asian and Middle East populations appears to be associated with the lower incidence of inflammatory diseases [30] . Recent studies indicate that PA has a strong antiinflammatory effect through inhibition of tissue necrosis factor α (TNF-α)-induced elevation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and ameliorates colitis in an experimental rat model [30] .…”
Section: Antioxidant and Antiinflammatory Effects Of Pamentioning
confidence: 99%
“…It has been proposed that consumption of large amounts of CFA by the Asian and Middle East populations appears to be associated with the lower incidence of inflammatory diseases [30] . Recent studies indicate that PA has a strong antiinflammatory effect through inhibition of tissue necrosis factor α (TNF-α)-induced elevation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and ameliorates colitis in an experimental rat model [30] . Likewise, BassaganyaRiera et al provided in vivo molecular proof that PA ameliorated experimental inflammatory bowel disease by modulating T-cell and macrophage function through peroxisome proliferator activated receptors (PPAR-γ) and δ-dependent mechanisms [31] .…”
Section: Antioxidant and Antiinflammatory Effects Of Pamentioning
confidence: 99%